2010
DOI: 10.1002/ange.200905997
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity in Perovskites with s0 A‐Site Cations: Toward Near‐Room‐Temperature Multiferroics

Abstract: Magnetic ferroelectric (FE) materials (that is, multiferroics) have received much attention and can have wide technological applications owing to the possibility of controlling their electric properties and their magnetic properties by electric fields. [1, 2] An important class of multiferroic and FE [3] materials is based on perovskites, ABO anion). In most cases, the A cations are small, so that t < 1 and the AÀO bonds are too long to maintain the ideal cubic structure. Consequently, the A cation moves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[11][12][13] Herein, we report on the stabilization of new perovskite oxides (In 1Ày Mn y )MnO 3 (1/9 y 1/3) using a high-pressure high-temperature technique. Not only is the discovery of new simple ABO 3 perovskites extremely rare these days, but (In 1Ày Mn y )MnO 3 perovskites are very unusual in a few ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Herein, we report on the stabilization of new perovskite oxides (In 1Ày Mn y )MnO 3 (1/9 y 1/3) using a high-pressure high-temperature technique. Not only is the discovery of new simple ABO 3 perovskites extremely rare these days, but (In 1Ày Mn y )MnO 3 perovskites are very unusual in a few ways.…”
mentioning
confidence: 99%
“…[ 12 (Z = 1), where A, B1, and B2 stand for the A site and two B sites of the perovskite structure. The structural analysis showed that all the oxygen sites are fully occupied.…”
mentioning
confidence: 99%
“…In the first place, the ionic radius of Mg 2+ is larger than that of Ti 4+ , so the Bsite Mg 2+ substitution can increase the relative ionic displacement and thus improve the dipole polarizability [40]. In the second place,the substitution of Mg 2+ causes the distortion of TiO 6 octahedra, which conduces to the improvement of P max of Bi(Mg 0.5 Ti 0.5 )O 3 doped thin films [41]. What's more, the remnant polarization of the thin films increases slightly from 6.75 to 8.60 μC/cm 2 with the addition of BMT from 0.3 to 0.6.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] Presently, applications of ferroelectrics are dominated by inorganic perovskite-type materials, such as lead zirconate titanate (PZT) and barium titanate (BTO). [8][9][10][11] It should be noted that ferroelectricity was first discovered in an organic crystal, Rochelle salt, 12 and later some other molecular crystals were found to be ferroelectric, such as triglycine sulfate and thiourea. The mechanism of most molecular ferroelectrics comes from order-disorder transition, while that of inorganic perovskite ferroelectrics comes from displacement of cations and/or anions.…”
Section: Introductionmentioning
confidence: 99%